Reliability and validity of Turkish version of Biological Rhythms Interview of Assessment in Neuropsychiatry - (:unkn) unknown (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2012)
Objective: In this study, it is aimed to perform the validity and reliability of the Turkish version of Biological Rhythms Interview of Assessment in Neuropsychiatry. Methods: The study was performed with 79 bipolar type-I disorder, 26 bipolar type-II disorder and 42 major depressive disorder patients attending to mood disorder clinics of three university hospitals and one state training hospital as well as 116 university students consisting healthy control subjects. The mean duration of the illness was 15.1 years for the bipolar groups and 9,3 years for the depressive group. For concurrent validity, Pittsburgh Sleep Quality Index was used. In the statistical analyzes, internal consistency coefficient, item-total score correlations, exploratory and confirmatory factor analyzes, correlation with the other scale and ROC curve were calculated. Results: The forward and back translation of the Biological Rhythms Interview of Assessment in Neuropsychiatry was performed, and linguistic equivalence was obtained with the scale prepared. In internal consistency, the Cronbach's alpha coefficient was found to be 0.899 and item-total correlation coefficients were between 0.239 and 0.747. In the exploratory factor analysis, a total of three factors representing 56.5% of the total variance were obtained and the themes of the factors were daily activities, sleep and eating habits and interpersonal relations. In the confirmatory factor analysis, confirmatory fit index was 0.932 and root mean square of approximation was 0.065. The correlation between Biological Rhythms Interview of Assessment in Neuropsychiatry and Pittsburgh Sleep Quality Index was found to be r=0.238. In the sensitivity and specificity analysis, the area under the ROC curve was 0.876. The scale discriminated mood disorder groups from the healthy control group. Conclusion: It is shown that the Turkish version of Biological Rhythms Interview of Assessment in Neuropsychiatry which is used in the assessment of circadian rhythm and functionality is reliable and valid.
Keywords: mood disorders; Biological Rhythms Interview of Assessment in Neuropsychiatry; reliability; validity; BIPOLAR DISORDER